Extra service sirn ; Black beauty ; Divine inspiration [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Tackles massage parlors in Metro Manila offering hospitality girl service; black Amerasians; and interview with Fr. Manoling Francisco about his composition being sung in Eucharistic celebrations.